Optimizing Economic Outcomes Through Information System Utilization: Enhancing Competency in Civil Servant Candidate Basic Training at South Sulawesi - Jamaluddin, Hamdana (International Journal of Economics Development Research (IJEDR), 2024)
System (LMS) in supporting competency development among Civil Service Candidates (CPNS) at the Human Resource Development Agency (BPSDM) in South Sulawesi Province. Using a mixed-methods approach, the research combines quantitative surveys of 89 CPNS participants with qualitative interviews of 20 participants to assess SIBANG’s impact on technical, managerial, and socio-cultural competencies. Quantitative results indicate that while SIBANG effectively supports technical competency development, the platform is less effective in enhancing managerial and socio-cultural skills, which require more interactive and hands-on learning methods. The regression analysis shows a positive but statistically insignificant relationship between SIBANG usage frequency and competency improvement, suggesting that additional factors, such as content interactivity and technical infrastructure, play a critical role. Qualitative findings highlight challenges such as connectivity issues, usability concerns, and a need for more practical learning tools within SIBANG. Based on these insights, the study recommends incorporating interactive features, enhancing technical support, and providing targeted guidance to optimize SIBANG’s potential as a comprehensive training tool. These improvements could enable SIBANG to better support the diverse competency needs of CPNS, contributing to the development of a skilled and adaptable civil service workforce.